Variation in susceptibility of field strains of three stored grain insect species to spinosad and chlorpyrifos-methyl plus deltamethrin on hard red winter wheat - Sehgal, Blossom; Subramanyam, Bhadriraju; Arthur, Frank H.; Gill, Bikram S. (My University, 2012)
Spinosad and chlorpyrifos-methyl plus deltamethrin efficacy at labeled rates on hard red winter wheat were evaluated against 11 field strains of the red flour beetle, Tribolium castaneum (Herbst); six strains of the sawtoothed grain beetle, Oryzaephilus surinamensis (L.); and two strains of the lesser grain borer, Rhyzopedha dominica (F.), collected mostly from farm-stored grain in Kansas. Adults were exposed to wheat treated with spinosad at 1 mg(active ingredient)/kg or chlorpyrifosmethyl plus deltamethrin at three plus 0.5 mg(active ingredient) /kg. Adult mortality was assessed after 7 and 14 d and progeny production after 42 d. Spinosad did not provide complete mortality or progeny suppression of T. castaneum and O. surinamensis field strains, but was effective against R. dominica strains. Chlorpyrifos-methyl plus deltamethrin produced complete mortality and progeny suppression of field strains all three species. The two least susceptible T. castaneum and O. surinamensis strains and the two R. dominica strains were chosen for dose-response tests only with spinosad. The LD99 values for T. castaneum and R. dominica field strains were similar to that of the corresponding laboratory strains. Corresponding values for the two O. surinamensis field strains were significantly greater (≈6 times) than the laboratory strain. The effective dose for progeny reduction (ED99) of only one R. dominica field strain was significantly greater (≈2 times) than the laboratory strain. The baseline susceptibility data of field strains of three insect species to spinosad will be useful for monitoring resistance development when this product is commercially released as a grain protectant.
Citation: Sehgal, B., . . . & Gill, B. (2012). Variation in Susceptibility of Field Strains of Three Stored Grain Insect Species to Spinosad and Chlorpyrifos-Methyl Plus Deltamethrin on Hard Red Winter Wheat. Journal of Economic Entomology, 106(4), 1911-1919. https://doi.org/10.1603/EC13083
Keywords: Stored-grain insects; Spinosad; Chlorpyrifos-methyl plus deltamethrin; Field strains; Mortality